Consumer Information-Seeking and Cross-Media Campaigns: An Interactive Marketing Perspective on Multi-Platform Strategies and Attitudes Toward Innovative Products - Hyunkoo Heo; Sinae Lee (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
This study investigates how consumers’ information-seeking motivation and perceptions of cross-media campaigns influence their attitudes toward innovative products. Drawing from the perspective of interactive marketing, it highlights the role of consumer–brand interaction in shaping product evaluation and acceptance. The findings indicate that when consumers perceive a product as highly innovative, they tend to experience both curiosity and uncertainty. This activates their need for information-seeking, which subsequently increases their engagement with cross-media campaigns designed with interactive marketing elements. Through this process, consumers develop more favorable attitudes toward the product. The results also reveal a significant dual mediation effect between perceived innovativeness and product attitude, mediated by the need for information-seeking and perception of cross-media campaigns. Although each path may not independently reach significance, the combined sequential mechanism—where consumers actively explore and interact with brand content—plays a critical role in shaping product attitudes.